Fading echoes - Hunter, Erin. (New York, NY : Harper, an imprint of HarperCollins Publishers, 2015)
As Dovepaw, Jayfeather, and Lionblaze strive to understand and fulfill the prophecy that promises them great power, the cats of the Dark Forest begin to teach battle skills and techniques to different Clan cats through dreams.
"Warriors adventure game inside"--Back cover.
4.8
5-8
5-8
630L
630L
Keywords: Cats -- Juvenile fiction; Prophecies -- Juvenile fiction; Dreams -- Juvenile fiction; Cats -- Fiction; Prophecies -- Fiction; Dreams -- Fiction; Cats -- Fiction; Prophecies -- Fiction; Dreams -- Fiction